Perceptions of Internship Doctors on Promotive and Preventive Health Services in Puskesmas (Community and Primary Health Care Center) - Mariatul Fadillah; Murwani Emasrissa Latifah (Faculty of Medicine, Public Health, and Nursing, 2018)
Background: Health care services are any efforts that are self-administered or done jointly within an organization to maintain and improve health, prevent and cure diseases and restore the health of individuals, families, groups and/or communities. Promotional and preventive services are conducted by individuals or groups in improving health and preventing the occurrence of outcomes unwanted by the community. Community Primary Health Care Centers (Puskesmas) are primary health care centers for the community which serve as the location of the new family doctors internship program in Indonesia.Objectives: The purpose of this study is to investigate the perception of internship doctors on the promotion and preventive services at the Puskesmas where they are placed for internship.Methods: This research is a quantitative analytical study with cross-sectional research design through the distribution of a questionnaire in the form of a Google survey form to all internship doctors in 571 Puskesmas in Indonesia. The questionnaire contains a list of questions that have been categorized according to the parent theory used, namely the Lawrence Green theory. The samples obtained in this study included 218 internship doctors.Results: From this study it was found that as many as 130 people (59.6%) of intern doctors who conducted promotive and preventive health services at Puskesmas came from State Universities. As many as 86 people (39.4%) of interns who conducted promotive and preventive health services at Puskesmas were 25 years old, with 143 (65.6%) females and 184 people (84.4%) unmarried. From the results of logistic regression analysis of Awareness Level, Knowledge Level, Time, Potential Revenue and Government Support, all factors have significant influence on the internship doctors’ perceptions on the promotive and preventive health care services (p<0.05).Conclusion: In this research, there are profiles and factors that significantly influence the internship doctor’s perceptions on health promotion and preventive services at Puskesmas.